Türk İş Hukukunda 625 sayılı Kanuna tabi olarak çalışanların hukuki durumu - Şen, Işıl (İstanbul Bilgi Üniversitesi, 2006)
[Abstract Not Available]
Legal situation of the workers who are employeed in accordance with 625th Law Under Turkish Labour Law